Diferencia entre revisiones de «Tensor deformación»

27 bytes añadidos ,  hace 7 años
{{ecuación|
<math>
\mathbf{D_mD}_m = \mathbf{E} = \frac {1}{2}(\mathbf{F}^{T}\mathbf{F}-\mathbf{1})</math>
||left}}
:O bien en función del campo de desplazamientos:
{{ecuación|
<math>\varepsilon_{ij} = {1 \over 2} \left ({\part u_i \over \part x_j} + {\part u_j \over \part x_i}+\sum_{k}{\part u_k \over \part x_i}{\part u_k \over \part x_j}\right)</math>
{{ecuación|
:<math>
\mathbf{D_eD}_e = \mathbf{e} = \frac {1}{2}(\mathbf{1}-\mathbf{F}^{-T}\mathbf{F}^{-1})
</math>
||left}}
121 505

ediciones